Investigation of effects of polymer semiconductor blends on threshold voltage tuning of field effect transistors - Tan, Zhen Hao. (2009)
In this project, inverters were fabricated using three different thiophenes (P3HT, PQT and PBTDT) as the semiconductor layer and were electrically tested. All three polymer based inverters showed good switching characteristics and gain of > 2. However, due to the positive threshold voltage, the switching voltage shifted to more positive which is larger than the VDD, which then rendered its useless in organic circuit due to unmatching VIN to VOUT. Hence, for inverters to be functionable, threshold voltage control is essential. The project then moved into fabricating OFETs using different weight composition of polymer blends, to investigate the effect on tuning threshold voltage.